Pemberian diet modifikasi komersial dan pengaruhnya terhadap asupan makanan dan status gizi pasien penyakit ginjal kronik prehemodialisis di RSUP DR. M. Djamil Padang - Pitri Balgis; Probosuseno Probosuseno; Herni Astuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2008)
Background: Chronic kidney disease causes progressive deterioration of kidney function and is commonly irreversible, leading to nausea and vomiting as a consequence of high ureum and creatinine in the blood. This condition results in declining appetite which greatly affects food intake and degrading nutritional status that causes high mortality among chronic kidney patients. Therefore efforts are made on how to increase intake of chronic kidney patients.Objective: To identify the effect of nutrition therapy through commercial diet modification to nutrition intake and status of pre-hemodialysis chronic kidney patients at DR. M. Djamil Hospital, Padang.Method: The study was a quasi experiment which used pre-test and post-test with control group design. Population of the study were all patients of pre-hemodialysis chronic kidney disease hospitalized at DR. M. Djamil Hospital of Padang. Samples were patients of pre-hemodialysis chronic kidney disease at internal medicine ward. The experiment group consisted of 11 patients who got modified diet within 6 days and control group consisted of 11 patients who got hospital standard diet with α = 0.05 and ß = 10%. The study were collected from January-March 2008. Data of intake were analyzed using Nutri Survey program. Statistical t-test and chi-square were used to identify the effect of commercial modified diet to food intake, nutritional status, and increase of ureum and creatinine. Absorption level was measured from the quantity of commercial nutrition used. Perception of the patients about commercial diet was obtained through questionnaires and analyzed to get the score.Results: The group with modified diet had better energy and protein intake than the group with hospital standard diet (p < 0.05). However, there was no significant difference in nutritional status, ureum and creatinine changes between patients who got modified diet and those who got hospital standard diet (p < 0.05). The result of analysis on perception of patients about commercial diet showed that patients could accept commercial diet.Conclusion: Commercial modified diet could increase intake of energy and protein of pre-hemodialysis chronic kidney patients.